2013
DOI: 10.1111/1744-9987.12146
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Elevated Cytokine Levels in Acute/Acute‐on‐Chronic Liver Failure Using Super‐Large Pore Albumin Dialysis Treatment: An In Vitro Study

Abstract: The removal of small water soluble toxins and albumin-bound toxins in acute liver failure patients (ALF) or acute-on-chronic liver failure (AocLF) patients has been established using extracorporeal liver support devices (e.g. Molecular Adsorbents Recirculating System; MARS). However, reduction of elevated cytokines in ALF/AocLF using MARS is still not efficient enough to lower patients' serum cytokine levels. New membranes with larger pores or higher cut-offs should be considered in extracorporeal liver suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 19 publications
1
16
0
1
Order By: Relevance
“…At the end, 3 case reports [15,16,17], 3 studies on animals [18,19,20], 11 in-vitro/ex-vivo studies [13,21,22,23,24,25,26,27,28,29,30,] and 6 randomized clinical trials/observational studies [14,31,32,33,34,35] fulfilled optimum criteria. The main results deriving from this pool constitute this review.…”
Section: Introductionmentioning
confidence: 99%
“…At the end, 3 case reports [15,16,17], 3 studies on animals [18,19,20], 11 in-vitro/ex-vivo studies [13,21,22,23,24,25,26,27,28,29,30,] and 6 randomized clinical trials/observational studies [14,31,32,33,34,35] fulfilled optimum criteria. The main results deriving from this pool constitute this review.…”
Section: Introductionmentioning
confidence: 99%
“…MARS has been shown to provide both protein- and albumin-bound toxin removal, including ammonium, biliary salts, urea, drug metabolites, and others, and in some cases of acute liver injury can help avoid the need for LT [3,4]. Also, it has been reported that MARS decreases serum concentrations of inflammatory mediators, which are considered to be a critical component of the neuropsychiatric findings associated with hepatic encephalopathy [57]. …”
Section: Discussionmentioning
confidence: 99%
“…The new charcoal adsorbent Hepalbin was scaled up (=Hepalbin‐Cluster 12 ; Albutec GmbH, Rostock, Germany) and tested in a 6 h albumin recirculation model against both standard MARS adsorbents (diaMARS IE250; diaMARS AC250) and empty adsorbents as control ( N = 3). The 6 h treatment was realized as previously described and was modified to neglect effects of hemofilter passage. Removing the hemofilter – acting as a first barrier of toxin transfer – from the two‐compartment model leads to the highest possible toxin load for adsorbents within the models’ limits.…”
Section: Methodsmentioning
confidence: 99%
“…We found that widening the pore size of a membrane increases the removal of strongly albumin bound toxins (e.g. indirect bilirubin) as well as cytokine removal in albumin dialysis .…”
mentioning
confidence: 90%